2000
DOI: 10.1002/1096-9098(200007)74:3<181::aid-jso3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Prospective phase II trial of alternating intravesical Bacillus Calmette-Gu�rin (BCG) and Interferon alpha IIB in the treatment and prevention of superficial transitional cell carcinoma of the urinary bladder: Preliminary results

Abstract: Alternating intravesical BCG and IFN is effective and well tolerated therapy for superficial TCC of urinary bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The final number of papers included in the meta-analysis was 30, list of studies excluded and reasons were shown in Figure 1. Of these, nine were identified to explore the necessity of BCG maintenance [16-24], seven investigate the efficacy of low-dose BCG [5-7,25-28], and the remainders address the effects of BCG combination therapy [29-42]. There were 21 randomized-controlled trails (RCTs), eight retrospective studies and one case-series study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final number of papers included in the meta-analysis was 30, list of studies excluded and reasons were shown in Figure 1. Of these, nine were identified to explore the necessity of BCG maintenance [16-24], seven investigate the efficacy of low-dose BCG [5-7,25-28], and the remainders address the effects of BCG combination therapy [29-42]. There were 21 randomized-controlled trails (RCTs), eight retrospective studies and one case-series study.…”
Section: Resultsmentioning
confidence: 99%
“…The severe side-effects that can be easily recognized by both patients and researchers made most of studies failed to use double-blind method, which should be responsible for the low-quality of included RCTs. Only 1 retrospective studies which didn’t adopt appropriate protocol for treatment assignment and used historical series as controls were recognized as low quality case-series study (level of evidence: 4) [42]. The results of quality assessment were listed in Additional file 1: Table S2 and Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…This includes maintenance BCG therapy, combining BCG with other agents such as interferon and the use of other chemotherapeutic agents instead of BCG. We have previously published the result of two investigational approaches to reduce NMIBC recurrence after BCG therapy by either alternating intravesical BCG with interferon on a weekly basis[ 8 ] or combining BCG and Interferon. [ 9 ] Compared to published literature, our results were similar to the results obtained with BCG alone.…”
Section: Introductionmentioning
confidence: 99%